Health-Related Quality of Life of Children and Adolescents With Congenital Hyperinsulinism – A Scoping Review - Kristensen, Kaja; Quitmann, Julia; Witt, Stefanie (Frontiers in Endocrinology, 2021)
Despite improvements in diagnosis and therapeutic advances in treatment, congenital hyperinsulinism (CHI) remains a severe disease with high patient impairment. We aimed to review the literature on Health-related Quality of Life (HrQoL) in children and adolescents with congenital hyperinsulinism and summarize the findings. For this scoping review, a literature search was conducted in PubMed and Web of Science in May 2021. Inclusion and exclusion criteria for the selection of articles were defined a priori. Two hundred and forty-five (245) articles were identified through the search and screened on the basis of title and abstract. The full texts of forty articles were then assessed. Finally, four articles (published 2012-2020) describing Health-related Quality of Life in children and adolescents with congenital hyperinsulinism were included. The study designs were heterogeneous and included cross-sectional observational studies (n=2), clinical trials (n =1), and case reports (n=1) with different sample sizes. Three studies were conducted in European countries and one in Japan. The results for Health-related Quality of Life revealed inconsistencies. There are only a few studies looking at Health-related Quality of Life in children and adolescents with congenital hyperinsulinism. To gain a comprehensive understanding of the impact of congenital hyperinsulinism on Health-related Quality of Life in children and adolescents, it is necessary to use both generic and condition-specific instruments to measure Health-related Quality of Life of young patients in larger samples, to collect longitudinal data, and to consider qualitative research approaches.